The DevelopingOf Electronic Teaching Media and Programming Using Printed Circuit Board Solventing - Rahmat Hidayat; Reza Setiawan; Vera Pangni Fahriani; Enjang Ahmad Juanda; Rusman (International Journal of Science, Technology & Management, 2020)
Karawang is one of the regency in West Java having many industrial area in Indonesia.One of the industrial field is electronic industry. This condition gives a chance to the graduatees of vocational High School students, especially electro major study, to gain an occupation and develop the entrepeneurship in the field of electronic appliances industry in Karawang. This research uses the methods of “rancang bangun”. Sequencely, the method is a neccesity of identification needed. Then, this neccessity is analysed to obtain the specifically component. Furthermore, it is conducted soft and hard applicance design, making and testing. The result working from PCB based on the direction from a microcontroller Atmega8 which have to control the servo motor spin and calcuyate the process timing device work. Before the program is undergone, the user have to reset the timer process solventing on the menu that can be set through LCD display. After the program is undergone, so the device will be working as the well made program.Timer will be working as fast as possible after being pressed the “run” button. When the solventing has achieved the setting value or mark, so the microcontroller will direct the step timer motor to stop working on and the buzzer will stop ringing until the reset button pressed or power bottom turning down.